Strategies to Improve the Thermoelectric Figure of Merit in Thermoelectric Functional Materials - Sun, Yan; Liu, Yue; Li, Ruichuan; Li, Yanshuai; Bai, Shizheng (Frontiers in Chemistry, 2022)
In temperature difference power generation, electric refrigeration and integrated circuit and so on, the thermoelectric functional materials in recent years have been widely concerned. In this paper, the design and research progress of thermoelectric materials around lifting ZT value in recent years are reviewed. By optimizing the carrier concentration to improve the Seebeck coefficient, the steady improvement of carrier mobility and the influence of energy band engineering on thermoelectric performance are discussed. In addition, the influence of lattice thermal conductivity on ZT value is also very important. We discuss the general law that the synergistic effect of different dimensions, scales and crystal structures can reduce lattice thermal conductivity, and introduce the new application of electroacoustic decoupling in thermoelectric materials. Finally, the research of thermoelectric materials is summarized and prospected in the hope of providing effective ideas for expanding the application and scale industrialization of thermoelectric devices.